Challenges Facing Primary School Teachers in the Implementation of the Regular Curriculum to Learners with Disabilities in Inclusive settings in Kisumu County - Ogadho, Willis Achola (JOOUST, 2017)
Teachers teaching in inclusive classrooms encounter the task of having to adapt the curriculum to suit learners with different categories of disabilities in inclusive classroom settings. Hence, they are faced with numerous challenges. Statistics indicated that Kisumu County had a dropout rate of272 (40.7%) of learners with disabilities that enrolled in inclusive primary schools between the years 2010 and 2014.with a progression rate of 0.3% to post primary institutions in spite of having 245 (54%) teachers trained in inclusive education and the Kenya governments policy on inclusive education. The dropout rate and the low progression rate was a concern to education stakeholders in Kisumu County particularly the parents. This study was therefore designed to investigate the challenges encountered by the teachers in the implementation of the regular curriculum in the inclusive settings in Kisumu County. The objectives of the study were to; determine the suitability of the regular primary school curriculum to learners with disabilities in inclusive classrooms, determine the influence of learning barriers on curriculum implementation and establish attempts made to overcome these challenges. A conceptual framework adapted from Hilda Taba's curriculum model of 1962 guided the study. This study used correlation survey design, which utilized research instruments such as questionnaires, interview schedules, Focus Group Discussion guide, observation schedule and document analysis for collecting data. The study population comprised of 250 teachers, 25 Head teachers (HIT), 8 County Quality Assurance and Standards Officers (CQASO) and 6 Educational Assessment and Resource Coordinators (EARC). The study sample size was 225 teachers, 22 Head teachers (HT), 7 CQASO and 5 EAR CS after taking l 0% of the population for piloting. Both saturated and cluster sampling techniques were used to select the sample population. The 30% rule of cluster sampling technique was used to select schools for observation giving a total of 6 schools while stratified and random sampling techniques were used to select the classes and the teachers for observation respectively. The stratum were defined as lower (classes I, 2, 3) Middle (classes 4, 5) and upper (classes 6, 7) for which random sampling was used to choose one class for each strata giving a total of 18 classes and 18 teachers for observation. Face and content validity of the instruments were determined by seeking opinion from the lecturers and incorporating their suggestions in line with the study objectives. Reliability was determined through test-retest procedure. The instruments were presented to the respondents twice at an interval of two weeks and the scores correlated through Spearman Rank Correlation Coefficient. There was a high significant correlation (r= 0.8, p<.05) implying that the instruments were reliable. Quantitative data was analyzed using frequency counts, percentages and mean. Qualitative data were transcribed and reported in themes. Findings of the study showed that teachers encountered challenges in adapting the regular primary school curriculum to respond to the needs of learners with special needs and that barriers within the inclusive classrooms were found to influence curriculum implementation while attempts made to address the challenges faced by the teachers were found to have no impact on curriculum implementation. The research recommends that teacher education curricula (pre-service and in-service) and teachers' professional development should be reviewed to prepare teachers for an inclusive education system. The findings of the study might be used by agencies such as the Ministry of Education Science and Technology and Kenya Institute of Curriculum Development to develop a curriculum responsive to the needs of learners with disabilities in an inclusive classroom. Most importantly, further research should be conducted to better understanding of the complex relationship between the teachers level of' preparedness and the ability to adapt the curriculum to accommodate learners with disabilities.